2020
DOI: 10.1177/2042018820935771
|View full text |Cite
|
Sign up to set email alerts
|

Plant-derived oleanolic acid ameliorates markers of subclinical inflammation and innate immunity activation in diet-induced pre-diabetic rats

Abstract: Aims: Sub-clinical inflammation during pre-diabetes is one of the predisposing factors that facilitates the progression of pre-diabetes to type 2 diabetes. The administration of oleanolic acid (OA) with or without dietary intervention ameliorates the metabolic and cardiovascular complications in diet-induced pre-diabetes animal models of pre-diabetes. This study aimed to investigate whether OA can also suppress immune activation and ameliorate pro-inflammatory markers. Methods: Pre-diabetes was induced by feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 66 publications
(88 reference statements)
0
15
0
Order By: Relevance
“…The intake of the triterpenoid-rich oil improved both the oral glucose (GTT) and insulin tolerance tests (ITT). In fact, OA has been shown to coadjuvant metformin to ameliorate the consequences of pre-diabetes in Sprague–Dawley rats a high-fat high carbohydrate diet for 20 weeks [ 153 ]. According to these authors OA improved lipid metabolism, decreased plasma proinflammatory cytokines, as wells as C-reactive protein, fibrinogen and CD40L in the animals.…”
Section: Biological Activity Of Oamentioning
confidence: 99%
See 1 more Smart Citation
“…The intake of the triterpenoid-rich oil improved both the oral glucose (GTT) and insulin tolerance tests (ITT). In fact, OA has been shown to coadjuvant metformin to ameliorate the consequences of pre-diabetes in Sprague–Dawley rats a high-fat high carbohydrate diet for 20 weeks [ 153 ]. According to these authors OA improved lipid metabolism, decreased plasma proinflammatory cytokines, as wells as C-reactive protein, fibrinogen and CD40L in the animals.…”
Section: Biological Activity Of Oamentioning
confidence: 99%
“…Obese mice fed a high-fructose diet presented increased RNA expression of TNFα and MCP-1 in white adipose tissue and liver, which was ameliorated after being fed pomace olive oil rich in tritepenes, including OA [ 96 , 152 , 161 ]. In addition, Gamede et al [ 153 ] found decreased plasma proinflammatory cytokines, including TNF-α and IL-1β in Sprague Dawley rats fed a high fat, high carbohydrate diet after a 20-week treatment with OA.…”
Section: Biological Activity Of Oamentioning
confidence: 99%
“…The Animal Research Ethics Committee at the University of KwaZulu‐Natal (ETHICS#: AREC/086/018D) approved all animal experiments. Before being exposed to the experimental diets, the animals were permitted to acclimate to their new habitat for 1 week while eating standard rat chow and drinking tap water 21 . Procedures involving animal care were carried out in accordance with the institutional guidelines for animal care of the University of KwaZulu‐Natal, which adhere to the principles and guidelines of the Canadian Council on Animal Care.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the trial, all animals were anesthetized for 3 min with isoflurane (100 mg/kg; Safeline Pharmaceuticals Pty Ltd, Roodeport, South Africa) administered in a gas anesthetic chamber (Biomedical Resource Unit, UKZN, Durban, South Africa) 21 . Blood was obtained from unconscious rats through heart puncture and then injected into separate pre‐cooled heparinized containers.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibitory activity of OA on pro-inflammatory cytokines may ameliorate the progression of pre-diabetes state into type 2 diabetes by diminishing subclinical inflammation. OA significantly reduces the expression of TNF-α, IL-1β, NF-kB, and CD40L in pre-diabetic animals; CD40L is an inflammatory mediator belonging to the TNF family that interacts with immune cells such as T cells and induces the production of chemokines, leading to inflammatory responses [ 155 ]. A frequent complication of diabetes is the increased incidence of chronic kidney disease; Gamede et al have continued their research by assessing the alleviating effect of OA on kidney-affected pre-diabetic rats.…”
Section: Oleanolic Acidmentioning
confidence: 99%